THE NEW GROVE DICTIONARY OF MUSIC AND MUSICIANS edited by Stanley Sadie, Macmillan Publishers Ltd., London, 1981, 20 vols., 18 000 pp., 4 500 illustrations, 3 000 music examples, £850.00. - Rycroft, David K. (International Library of African Music, 1983)
pages: 115-117
Keywords: African Music